The MATCH project: collaboration between academia and industry - Craven, Michael P. (Association of British Healtcare Industries, 2004)
The university sector offers innovative research initiatives which industry should be tapping. Michael Craven, Senior Research Fellow at the University of Nottingham, reports on a unique collaboration between academia and industry that is helping companies assess the value of medical technology.